THE CREATIVE PATH OF THE HONORED ARTIST OF UKRAINE SERHIY VIKTOROVYCH NAYENKA AND HIS ACTIVITIES AT THE LVIV CHOREOGRAPHY SCHOOL - Мокрій, Роксолана (SWorldJournal, 2023)
The article examines the creative path of the Honored Artist of Ukraine Serhiy Nayenko from childhood and his interest in choreography to studying with leading ballet artists at the choreographic school. The reasons for choosing work in favor of the Lviv